This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Doing it the long way (also the only way I know) using digamma function .
S = n = 0 ∑ ∞ 1 + n 2 1 = n = 0 ∑ ∞ ( n − i ) ( n + i ) 1 = 2 i n = 0 ∑ ∞ ( n + i 1 − n − i 1 ) = 1 + 2 i n = 1 ∑ ∞ ( n + i 1 − n − i 1 ) = 1 + 2 i ( ψ ( 1 − i ) − ψ ( 1 + i ) ) = 1 + 2 i ( π cot ( π i ) − i 1 ) = 1 + 2 π coth π − 2 1 ≈ 2 . 0 7 7 Digamma function ψ ( z + 1 ) = − γ + k = 1 ∑ ∞ ( k 1 − k + z 1 ) where γ is the Euler-Mascheroni constant. Using ψ ( 1 − z ) − ψ ( z ) = π cot ( π z ) and ψ ( 1 + z ) = ψ ( z ) + z 1
Problem Loading...
Note Loading...
Set Loading...
The Fourier series of e x at x = ± π is π 1 sinh π + π 2 sinh π n = 1 ∑ ∞ 1 + n 2 1 = 2 e π + e − π Solving for ∑ n = 0 ∞ 1 + n 2 1 gives 2 1 ( 1 + π coth π ) ≈ 2 . 0 7 6 6 7